2018
DOI: 10.1016/j.ultsonch.2018.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis, growth process, characterisation of a nanourchin-structured α-MnO2 and their application on ultrasonic-assisted adsorptive removal of cationic dyes: A half-life and half-capacity concentration approach

Abstract: Textile dyes pose a serious threat in terms of water pollution due to its complex aromatic structures and poor degradability. In order to reduce the toxic effects of Crystal Violet (CV) and Methylene Blue (MB), an ultrasonic-assisted dye adsorption using urchin like α-MnO nanostructures was studied. The adsorbent was synthesised by hydrothermal method at low-temperature. The crystallinity and morphology were determined to investigate the growth mechanism of α-MnO nanourchins which consists of two main stages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…The literature review suggested that significant research over the aqueous media has been conducted to remove numerous dyestuffs including methylene blue from waters. Among the most commonly employed methods for decolorization and removal of dyes include both traditional treatment and non-traditional methods, e.g., adsorption (Abraham et al 2018;Jamal et al 2016;Shim et al 2019;Xiong et al 2020), biological treatments (Jafari et al 2017;Wang et al 2012), biosorption (Sebeia et al 2019;Zhai et al 2019), electro-coagulation (de Carvalho et al 2015Nippatla and Philip 2019), advanced oxidation processes (Bao et al 2018;Kang et al 2019;Liang et al 2012;Qu et al 2014), photocatalytic degradation (Gagrani et al 2018;Nanda et al 2016;Zhao et al 2018), ozonation (Hama Aziz et al 2018, chemical precipitation and membrane technology (Ghaemi and Safari 2018;Liu et al 2018), ultrafiltration (Ouni and Dhahbi 2010), ceramic membrane-based technologies on amorphous silica (Abdelrazek and Barakat 2016) and also degradation based on sonochemical method (Abbasi and Asl 2008). However, complete removal of dyes along with their derivatives is still a challenge with single or traditional treatment by which the decolorization can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The literature review suggested that significant research over the aqueous media has been conducted to remove numerous dyestuffs including methylene blue from waters. Among the most commonly employed methods for decolorization and removal of dyes include both traditional treatment and non-traditional methods, e.g., adsorption (Abraham et al 2018;Jamal et al 2016;Shim et al 2019;Xiong et al 2020), biological treatments (Jafari et al 2017;Wang et al 2012), biosorption (Sebeia et al 2019;Zhai et al 2019), electro-coagulation (de Carvalho et al 2015Nippatla and Philip 2019), advanced oxidation processes (Bao et al 2018;Kang et al 2019;Liang et al 2012;Qu et al 2014), photocatalytic degradation (Gagrani et al 2018;Nanda et al 2016;Zhao et al 2018), ozonation (Hama Aziz et al 2018, chemical precipitation and membrane technology (Ghaemi and Safari 2018;Liu et al 2018), ultrafiltration (Ouni and Dhahbi 2010), ceramic membrane-based technologies on amorphous silica (Abdelrazek and Barakat 2016) and also degradation based on sonochemical method (Abbasi and Asl 2008). However, complete removal of dyes along with their derivatives is still a challenge with single or traditional treatment by which the decolorization can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Langmuir [ 37 ] (Equation (7)) and Freundlich [ 38 ] (Equation (8)) isotherms are widely used in fitting the dye adsorption in textile dyeing. where [ D ] f (g g − 1 ) and [ D ] s (g L − 1 ) are the dye concentration in the fibre and dye solution at equilibrium time; [ S ] f (g g − 1 ) is the Langmuir constant related to adsorption capacity; K L is the Langmuir equilibrium constant.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that nano-sized MnO2 and hydrothermal carbon have good adsorption properties for organic dyes [65,66] . The characterization proved that we have prepared MnO2 loaded hydrothermal carbon-coated PAN nanofiber membranes successfully and the AC/MnO2/PAN nanofibers had excellent adsorption capacity for cationic dyes.…”
Section: Mechanism Of Mb Removal By Ac/mno 2 / Pan Fibersmentioning
confidence: 99%